2023
DOI: 10.1002/eat.23880
|View full text |Cite
|
Sign up to set email alerts
|

Non‐suicidal self‐injury, suicidal thoughts and behaviors in individuals with an eating disorder relative to healthy and psychiatric controls: A systematic review and meta‐analysis

Abstract: Objective: Eating disorders (ED) may be associated with an increased prevalence of non-suicidal self-injury (NSSI) and suicidal thoughts and behaviors (STBs) relative to healthy (HC) and psychiatric (PC) controls. However, precise estimates of differences in prevalence between individuals with EDs and controls are unclear. We compared the prevalence of NSSI, suicidal ideation (SI), suicide attempts (SA), and deaths by suicide in controls and individuals with EDs.Method: We searched MEDLINE, PsycINFO, EMBASE, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Extending findings from Fox et al (2019), results suggest that self‐harm and ED behaviors may be viewed on a continuum. Current classifications of ED behaviors and NSSI as entirely distinct may hinder the importance of acknowledging the self‐harm component that our study and others support as highly comorbid with ED behaviors (e.g., Germain & Hooley, 2012; Sohn et al, 2023). Moreover, the strong indications of suicidal cognitions when engaging in restrictive behaviors underline the elevated prevalence of suicide among those with eating disorders (Arcelus et al, 2011; Fichter & Quadflieg, 2016), as restrictive eating is transdiagnostic (Lowe et al, 2018), and associated suicide‐related thoughts and intentions may be considered similarly.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Extending findings from Fox et al (2019), results suggest that self‐harm and ED behaviors may be viewed on a continuum. Current classifications of ED behaviors and NSSI as entirely distinct may hinder the importance of acknowledging the self‐harm component that our study and others support as highly comorbid with ED behaviors (e.g., Germain & Hooley, 2012; Sohn et al, 2023). Moreover, the strong indications of suicidal cognitions when engaging in restrictive behaviors underline the elevated prevalence of suicide among those with eating disorders (Arcelus et al, 2011; Fichter & Quadflieg, 2016), as restrictive eating is transdiagnostic (Lowe et al, 2018), and associated suicide‐related thoughts and intentions may be considered similarly.…”
Section: Discussionmentioning
confidence: 57%
“…Participants reported higher knowledge that they would die sooner due to NSSI and restrictive eating compared to binge eating. Finally, Germain & Hooley, 2012;Sohn et al, 2023). Moreover, the strong indications of suicidal cognitions when engaging in restrictive behaviors underline the elevated prevalence of suicide among those with eating disorders (Arcelus et al, 2011;Fichter & Quadflieg, 2016), as restrictive eating is transdiagnostic (Lowe et al, 2018), and associated suiciderelated thoughts and intentions may be considered similarly.…”
Section: Comparisons Of Suicide and Death Related Cognitions And Inte...mentioning
confidence: 99%
“…Three previous meta-analyses on NSSI in individuals with EDs or disordered eating have been conducted within the past decade. One meta-analysis (using odds ratios) only included studies with a control group, included individuals without a confirmed ED diagnosis (i.e., self-reported symptoms) and focused specifically on NSSI, however, it is unclear how this was defined (Sohn et al, 2023). This previous study found that individuals with an ED are 6.85 times more likely to report NSSI compared to healthy controls.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…Included studies must have examined prevalence of self-injurious behaviors, therefore case-control studies that created groups based on the presence of NSSI (e.g., Doktorova & Demuthova, 2021) were ineligible for inclusion. (Amiri & Khan, 2023;Cucchi et al, 2016;Sohn et al, 2023) were also reviewed for any manuscripts that met inclusion criteria but did not appear within database searches.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…AN-associated mortality ranges from 2 to 8%, which is the highest mortality rate for a psychiatric disorder [7,13], mainly because of suicide and organic complications [1,14,15]. Mortality during initial stabilization stages is proportional to the degree of malnutrition [16] and is related to the use of intensive care facilities [17].…”
Section: Introductionmentioning
confidence: 99%